Prospects for NK-based immunotherapy of chronic HBV infection - Jin, Xiaomeng; Bi, Jiacheng (Frontiers in Immunology, 2022)
Effective and long-term treatment is required for controlling chronic Hepatitis B Virus (HBV) infection. Natural killer (NK) cells are antiviral innate lymphocytes and represent an essential arm of current immunotherapy. In chronic HBV (CHB), NK cells display altered changes in phenotypes and functions, but preserve antiviral activity, especially for cytolytic activity. On the other hand, NK cells might also cause liver injury in the disease. NK -based immunotherapy, including adoptive NK cell therapy and NK -based checkpoint inhibition, could potentially exploit the antiviral aspect of NK cells for controlling CHB infection while preventing liver tissue damage. Here, we review recent progress in NK cell biology under the context of CHB infection, and discuss potential NK -based immunotherapy strategies for the disease.